Learn Adobe Photoshop CC for visual design : Adobe Certified Associate exam preparation - Schwartz, Rob, 1969- (Pearson Education, Inc., 2018)
As the most image-editing application on the market today, Adobe Photoshop is an indispensable part of any creative designer's toolkit. Mastering Photoshop for photo retouching or general design work should be the first step on your path to a career i the visual design field. Learn Adobe Phtoshop CC by building cool creative projects that teach you how to: Fix common problems with photographs ; Colorize black and white photos ; Design eye-catching invitations and fliers ; Create fantastic composite images by combining elements from different photos ; Design your own wallpaper for your computer or phone. This study guide uses more than 13 hours of video integrated with text to help you gain real-world skills that will get you started in your career in visual design using Adobe Photoshop CC. It lays the foundation for taking the Adobe Certified Associate (ACA) certification exam and helps prepare you for an entry-level position in a competitive job market.